Administrative and legal guarantee of the rights and legitimate interests of Ukrainian citizens in the field of public administration in Ukraine - Добош, Зоряна; Dobosh, Zoryana (Видавництво Львівської політехніки, 2023)
Стаття присвячена проблемі адміністративно-правового гарантування прав та законних інтересів громадян України у сфері публічного управління в Україні. Особливу увагу присвячено аналізу прав та законних інтересів особи у сфері публічного управління як предмета адміністративно-правового гарантування в Україні. Встановлено, що джерелом гарантування прав особи у сфері публічного управління є держава. Інші інституції держави, що виступають суб’єктами адміністративно-правового гарантування прав особи у сфері публічного управління, транслюють її волю, наділені державою спеціальною компетенцією, ефективними засобами гарантування прав особи. У статті проаналізовано особливості поєднання публічного інтересу та приватних законних інтересів окремих фізичних осіб, теорії дуалізму приватного та публічного інтересу в рамках суб’єктивного публічного права, представлено аналіз категорії «публічні законні інтереси», структуру суб'єктивних публічних прав. З’ясовано, що категорія суб’єктивне право у публічно-правовій сфері є ширшою за категорію суб’єктивне публічне право. Особливу увагу присвячено різновидам суб’єктивних публічних прав людини, оскільки їхнє задоволення є найважливішим предметом адміністративно-правового гарантування з боку держави, зокрема й через механізм судового контролю. Особлива увага присвячена аналізу публічно-громадянських, публічно-політичних, публічно-соціальних прав. Виокремлено позитивні та негативні публічні, загальні та спеціальні права у досліджуваній сфері. Відзначено, що практична реалізація адміністративно-правових гарантій прав особи потребує залучення широкого кола інституцій держави, наділених потрібною компетенцією задля формування умов, реалізації засобів, націлених на гарантування можливості втілення прав особи в життя та, у разі потреби, їхнього захисту. Охарактеризовано особливості гарантування правових можливостей людини, систему таких гарантій. Наголошено, що здійснюючи гарантування широкого спектру правових можливостей, держава повинна зосередитися на виробленні в умовах війни чіткого механізму протидії зловживанню правом у сфері публічного управління.

The article is devoted to the problem of administrative-legal guarantee of the rights and legitimate interests of Ukrainian citizens in the sphere of public administration in Ukraine. Special attention is devoted to the analysis of the rights and legitimate interests of a person in the field of public administration as a subject of administrative and legal guarantees in Ukraine. It has been established that the source of guaranteeing individual rights in the field of public administration is the state. Other institutions of the state acting as subjects of administrative and legal guarantee of the rights of the individual in the field of public administration, broadcasting his will, endowed by the state with special competence, effective means of guaranteeing the rights of the individual. The article analyzes the peculiarities of the combination of public interest and private legitimate interests of individual individuals, the theory of the dualism of private and public interest within the framework of subjective public law, presents an analysis of the category "public legitimate interests", and the structure of subjective public rights. It was found that the category of subjective law in the public legal sphere is wider than the category of subjective public law. Particular attention is paid to the types of subjective public human rights, since their satisfaction is the most important subject of administrative and legal guarantee by the state, in particular through the mechanism of judicial control. Special attention is devoted to the analysis of public-civil, public-political, public-social rights. Positive and negative public, general and special rights in the researched area are singled out. It was noted that the practical implementation of administrative and legal guarantees of individual rights requires the involvement of a wide range of state institutions endowed with the necessary competence to create conditions, implement means aimed at guaranteeing the possibility of implementing individual rights and, if necessary, their protection. The features of guaranteeing the legal rights of a person, the system of such guarantees are characterized. It is emphasized that while guaranteeing a wide range of legal opportunities, the state should focus on developing a clear mechanism for countering the abuse of law in the field of public administration in wartime conditions.
Адміністративно-правове гарантування прав та законних інтересів громадян України у сфері публічного управління в Україні
Keywords: адміністративно-правове гарантування; права громадян; законні інтереси громадян; суб’єктивне публічне право; публічні правовідносини; публічний інтерес; публічне управління; administrative and legal guarantee; rights of citizens; legitimate interests of citizens; subjective public law; public legal relations; public interest; public management; 342.9/342.56